Effect of planting density on growth, yield related factors and profitability of rubber (Hevea brasiliensis Muell.Arg.) - Rodrigo, V.H.L. and others (Rubber Research Institute of Sri Lanka. Agalawatte, 1995)
Data available on an experiment on planting density of rubber in Kalutara region of Sri Lanka were analyzed in view of investigating how planting density affects yield, yield related factors and financial return. Experimenet comprised six planting densities from 400 to 920 trees per hectare and three clones PB 86, RRIC 101 and RRIC 103. Planting density has affected plant girth of all clones from fourth year onwards. Density effect on girth of RRIC 101 was higher than that of other clones. With increasing planting density bark thickness and number of latex vessel rings declined in all clones and relatively more marked in clone RRIC 101. Similarly, yield per tree per tapping decreased, but yield per hectare per tapping and net present value increased with the increase in density. Nevertheless, with only two years of yield data and also without knowing number of tapping days for each density tested, it is not possible to arrive at definite conclusions. Less variation in girth increment among different densities towards later stage of plant growth indicates that apparent effect of density in this stage could be a cumulative effect over the period but not the effect of this stage. No density effect on canopy light interception was evident. Available data justifies further investigations and it is suggested that more adoptability trials located in different agro-climatic regions are to be conducted using new clones before arriving at definite conclusions. In these srudies due consideration should be given to tappable stand, incidence of tapping panel dryness and tapping days.
Keywords: Agriculture; Yield; Hevea brasiliensis; Rubber